Thermal behaviour of partially encased column under combined compression and bending - Fellouh, Abdelkadir (2019)
In this paper, the advanced and simplified calculation methods are used to evaluate the fire resistance of eccentrically loaded partially encased composite columns (PEC). The work consists in developing of an efficient Non-linear 3-D finite element model (ANSYS) to investigate the behaviour of Pin-ended PEC eccentrically loaded at elevated temperature. The columns were tested under standard ISO834 fire. The buckling load is determined for several column heights 3; 4.5 and 6 m, by considering an eccentricity around the minor axis equal to 0,5.B; 1,0.B and 1,5.B (B section base). The numerical method presented here is compared with the simple calculation method Annex G of EN 1994-1-2. The results show that the load capacity of PEC column is reduced more than half in both condition, 50 min of fire exposure or increasing the load eccentricity by 0.5.B. Which is a fair conclusion to take the load eccentricity into consideration in structural fire design. The comparison results show a good agreement between the two methods at high fire ratings (R90 and R120), however at low fire rating (R30), the simple calculation method presents conservative results. It is to be concluded that the reinforcement has an influence on the thermal and mechanical behaviour of PEC column especially in combined compression and bending.